The Analysis of Customs Services Practice in the Conditions of the Eurasian Economic Union: Problems and Directions of Improvement - GUPANOVA, Yuliya Evgenievna; NEMIROVA, Gulzida Iksanovna; SUGLOBOV, Alexander Evgenievich (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018, 2018)
One of the most important directions of customs authorities development at the present time is improvement of the customs services sphere that will allow to influence on trade expenses decreasing for business, ensuring economic security, increasing of the country attractiveness in the investment side. The matters gain the special importance in the conditions of integration development within the Eurasian Economic Union as they demand coordination of legislative, methodological, methodical and a number of practical aspects of providing customs services in the united customs territory. The purpose of article is researching of customs services providing practice in conditions of the Eurasian Economic Union existence, identification of problems in this sphere and searching ways of their decision. Methods of the comparative, retrospective and system analysis, analogy, generalization and grouping were applied during article creating that has allowed to reveal key discrepancies in customs services providing in the countries of EEU and to designate the possible directions of their improvement. The results received in article cover the specified conceptual framework in the explored sphere, the designated methodological approaches to improvement of customs procedures. These approaches take into account interests of the main consumers of customs services – participants of foreign economic activity.